Wasim (soil water balance model) - Hess, Tim; Parker, Alison; Quinn, Ruth; Rushton, Ken (Cranfield University, 2019)
A one-dimensional soil water balance model that partitions daily rainfall into evapotranspiration, surface runoff and drainage. Options allow irrigation to be scheduled according to rules, water table position to be simulated with field under drainage, and soil water salinity to be estimated. The installation package includes a user manual, technical manual and a tutorial with sample data. [Please note: superseded by new version - see below]
Keywords: water balance model'; 'evapotranspiration'; 'Hydrology'